Value of food loss in ASEAN countries and its relationship with economic growth - Jaroensathapornkul, J. (International Journal of Agricultural Technology, 2021)
The research finding showed that the Food Loss (FL) value as a percentage of GDP in Cambodia, Laos, Myanmar, and Vietnam (CLMV countries) which it was clearly shown higher than Indonesia, Malaysia, the Philippines, and Thailand. In particular, Cambodia revealed the highest FL value as a percentage of GDP at 1.60%, which implied the lower level of development in post-harvesting and processing technologies as well as transportation in CLMV countries, while in Thailand and Malaysia, the FL values as a percentage of GDP were only 0.17% and 0.07%, respectively. Furthermore, in seven of these countries rice showed the highest FL value, while for Malaysia palm oil showed the highest FL value. On the other hand, in Indonesia the FL value of the palm oil continually increased at an average of 16% per year. In the 2000s, the ratio increased dramatically in Indonesia, from 3.60% during 1991–2000 to 24.43% during 2001–2010. Apart from rice in CLMV countries, it was further discovered in CLMV countries that significant FL values could also be found for bananas, cassava, maize, sugar cane, and sweet potato. In addition, estimates from an econometric model implicitly showed that the economic growth of ASEAN countries occurred at the expense of a higher food loss value. Economic development should therefore not focus purely on the expansion of conventional GDP only, but should also consider sustainability. Each country should set forth a target of “inclusive economic growth”. To reduce loss from the production processes and marketing, it is suggested that the economic system called the “circular economy for food” should be adopted. The government should divert more investment toward R&D regarding post-harvesting technologies and logistics system development to minimize the loss of agricultural products